Evaluating hyperpigmentation: is invasion of the skin necessary? - Bardhi, Redina; Mokhtari, Mohsen; Ceresnie, Marissa; Suvarnarkar, Aashka; Hamzavi, Iltefat H.; Lim, Henry W.; Mohammad, Tasneem F.; Kohli, Indermeet (Frontiers in Photobiology, 2024)
Background: The combination of long wavelength ultraviolet A1 radiation (LWUVA1) and visible light (VL) has been shown to produce photodamage and the majority of organic sunscreens lack protection against this spectrum. Currently, established testing protocols for VL photoprotection are lacking. Objective: To compare pigmentation assessment methods, including Investigator's Global Assessment (IGA) scoring, Diffuse Reflectance Spectroscopy (DRS), and immunohistochemistry, to assess the utility of each in evaluating VL+LWUVA1 induced pigmentation.Methods: Anonymized IGA, DRS, and immunohistochemistry data for 37 subjects (Fitzpatrick skin phototypes IV-VI) was retrospectively analyzed for pigment evaluation.Pigmentation was induced on the subjects' backs with VL+LWUVA1 (0-0.5% UVA1) irradiation at a dose of 480 J/cm². Comparisons were made for all three assessment techniques between non-irradiated skin and VL+LWUVA1 irradiated skin, as well as between pure VL (0% UVA1) and VL+LWUVA1 (0.5% UVA1) irradiated sites. All comparisons were made for data collected approximately 24 hours after irradiation to evaluate persistent pigment darkening (PPD).Results: Among all 37 subjects, both IGA scores and DRS detected a statistically significant difference in PPD between irradiated and non-irradiated sites, as well as between VL+LWUVA1 and pure VL irradiated sites. However, MART-1/Melan-A did not indicate a statistically significant difference in PPD between irradiated and non-irradiated sites or between VL+LWUVA1 and pure VL irradiated sites.Conclusions: Subjective and objective noninvasive assessments were more sensitive in detecting VL+LWUVA1 induced pigmentation and should be preferred over invasive methods.